Cloudy Days : A First Look - Leed, Percy, 1968- (Minneapolis, MN, USA : Lerner Publications Company, an imprint of Lerner Publishing Group, Inc., 2024)
Some clouds are puffy, some clouds are thin, some carry rain, and some carry snow. With leveled text and engaging photographs, young readers are sure to love learning more about cloudy days.
Ages 5-8
Grades K-1
Keywords: Clouds -- Juvenile literature; Cloudiness -- Juvenile literature; Juvenile works